FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERNIKAHAN DINI DI DUSUN I DESA BARU KEC PANCUR BATU DELI SERDANG SUMATERA UTARA TAHUN 2017 - Meriati Bunga Arta Purba (Elisabeth Health Jurnal, 2019)
Based on the research by the Sexuality and Gender Study Center of University of Indonesia, the rate of early marriage in Indonesia is the second highest in Southeast Asian in which 2 million out of 7.3 million women below 15 years old are married and drop out from school. Early marriage hinders them from going to school, causes pregnancy and birth complication, impedes the achievement of KB (Family Planning) Program and increases divorce rate. Goals : The objective of the research was to discover the correlation of value of virginity, knowledge and trust with early marriage at Dusun I Desa Baru. Methods: This is an observational analytical research with cross sectional design. It was done at Dusun I Desa Baru, Pancur Batu Subdistrict from November, 2017 until February, 2018. The population covered the teenagers below 20 years old which was all taken as the research samples i.e. 139 people. The dependent variable was early marriage, while the independent variables were parent income, trust, knowledge and value of virginity. The data were collected through questionnaires. Multiple logistic regression testing was employed to analyze the data. Result : The research results demonstrated that the variable with the most dominant influence was parent income at p-value = 0.006 (p<0.05) and Exp. β value = 3.675, followed by the variable of trust at p-value = 0.027 (p<0.05) and Exp. β value = 2.368, the variable of knowledge at p-value = 0.003 (p<0.05) and Exp. β value 6.064, and the variable of virginity at p-value = 0.003 (p<0.05) and Exp. Β value = 6.064. Based on these results, it was concluded that f(y) was 97%. It indicated that the probability of the variables of parent income, trust, knowledge and virginity influenced early marriage of 97.7%. Conclusion: It is recommended that the local government cooperate with local Puskesmas, Religious Figures, and Parents to conduct counseling to improve people’s knowledge of the ideal age to get married, so that they can prevent from possible problems due to early marriage and provide their children parent income at early age the importance of protecting their virginity until they get married.